Integrated clinical treatment of gingival recession secondary to root perforation: case report. - Sonoda, Celso Koogi [UNESP]; Barioni, Sônia Regina Panzarini [UNESP]; Poi, Wilson Roberto [UNESP]; Pedrini, Denise [UNESP]; Saito, Célia Tomiko Matida Hamata; Pinheiro, Joao J V (My University, 2009)
Among the factors that influence the success of treatment of a root perforation, its location and possibility of contamination are determinant because the interaction of these 2 factors may result in significant periodontal injury. The management of cases of hard-to-reach contaminated perforations depends on the choice of an adequate technique. In the case reported in this article, controlled orthodontic tooth extrusion was successfully performed to treat gingival recession secondary to root perforation. The outcomes showed that this technique preserves the zone of attached gingiva, maintains the crown height, and prevents the involvement of the supporting bone tissue. The favorable clinical and radio?graphic conditions after 7 years of follow-up demonstrate the viability of this treatment approach.
Keywords: glass ionomer; adult; case report; denture; endodontics; female; follow up; gingiva; gingiva disease; gingivoplasty; human; incisor; injury; instrumentation; orthodontics; pathology; patient care; patient care planning; tooth crown; tooth root; treatment outcome; Adult; Denture Design; Denture, Partial, Fixed; Female; Follow-Up Studies; Gingiva; Gingival Recession; Gingivoplasty; Glass Ionomer Cements; Humans; Incisor; Orthodontic Appliance Design; Orthodontic Extrusion; Patient Care Planning; Patient Care Team; Post and Core Technique; Root Canal Preparation; Tooth Crown; Tooth Root; Treatment Outcome